Strengthening the Reporting of Observational Studies in Epidemiology – nutritional epidemiology (STROBE‐nut): An extension of the STROBE statement1. Issue 3 (September 2016) - Lachat, C.; Hawwash, D.; Ocké, M. C.; Berg, C.; Forsum, E.; Hörnell, A.; Larsson, C. l.; Sonestedt, E.; Wirfält, E.; Åkesson, A.; Kolsteren, P.; Byrnes, G.; et al.
Abstract: Concerns have been raised about the quality of reporting in nutritional epidemiology. Research reporting guidelines such as the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement can improve quality of reporting in observational studies. Herein, we propose recommendations for reporting nutritional epidemiology and dietary assessment research by extending the STROBE statement into Strengthening the Reporting of Observational Studies in Epidemiology – Nutritional Epidemiology (STROBE‐nut). Recommendations for the reporting of nutritional epidemiology and dietary assessment research were developed following a systematic and consultative process, co‐ordinated by a multidisciplinary group of 21 experts. Consensus on reporting guidelines was reached through a three‐round Delphi consultation process with 53 external experts. In total, 24 recommendations for nutritional epidemiology were added to the STROBE checklist. When used appropriately, reporting guidelines for nutritional epidemiology can contribute to improve reporting of observational studies with a focus on diet and health.